The Integration of Local Values into the Spatial Behavior of Traditional Architecture: A Case Study of the Traditional House of Ponorogo, East Java - Josephine Roosandriantini; Y.A. Widriyakara Setiadi; Veronica Sinawan (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2026)
Traditional architecture is not merely a physical manifestation of spatial needs; it also reflects the cultural and social values of the community through its spatial patterns. The aim of this research is to explore the integration of local values into spatial behavior within the traditional architecture of the rumah adat (traditional house) of Ponorogo, East Java. The presence of the traditional Ponorogo house serves as a representation of local wisdom that continues to endure amidst the dynamic changes of time. This study identifies and analyzes the relationships between local values—such as customary norms, Javanese cosmology, and social structures—and the spatial usage patterns and behaviors of the inhabitants. The research employs a qualitative-descriptive approach, using data collection techniques including direct observation, in-depth interviews with residents, and literature studies on the traditional architecture of Ponorogo and the behavioral patterns occurring within these traditional houses. The research findings reveal that spatial division in the Ponorogo traditional house is not merely functional but carries strong symbolic meanings. Spaces such as jogan, omah mburi, gandhok, pawon, senthong, and emperan illustrate social hierarchies and ritual functions in the lives of the Ponorogo community. Moreover, the building’s orientation, spatial forms, and layout reflect a deep connection with nature and Javanese spiritual teachings. This study focuses specifically on the Sinoman and Joglo Bucu house types. The research affirms that traditional architecture possesses complex behavioral dimensions that cannot be separated from the cultural context surrounding it. Understanding the integration of local values into spatial behavior in traditional architecture is expected to serve as a foundation for the preservation and development of architecture with strong local identity amid the currents of modernization